The effect of 12-week high-dose Colostrum Bovinum supplementation on immunological, hematological and biochemical markers in endurance athletes: a randomized crossover placebo-controlled study - Durkalec-Michalski, Krzysztof; Główka, Natalia; Podgórski, Tomasz; Woźniewicz, Małgorzata; Nowaczyk, Paulina M. (Frontiers in Immunology, 2024)
Background Bovine colostrum (COL) is assumed to be one of the strongest natural immune stimulants. Regular ingestion of COL may contribute to improved immune response in athletes exposed to high training loads. Methods Twenty-eight endurance-trained males aged 31.1 ± 10.2 years (body mass 81.9 ± 9.0 kg; height 1.82 ± 0.06 m) completed this randomized double-blind placebo(PLA)-controlled crossover study aimed at investigating the effect of 12-week COL supplementation (25gCOL·day-1) on resting (REST), exercise-induced (POST-EX), and short-term post-exercise recovery (REC; 1 h after test exercise) changes in selected saliva and blood immunoglobulins (Ig), white blood cell (WBC) count and differential; as well as blood hematological, nutritional status and muscle damage indices. The protocol assumed 4 study visits – before/after supplementation with COL (COLPRE and COLPOST) and PLA (PLAPRE and PLAPOST). During testing sessions, incremental rowing test to exhaustion and swimming-specific performance test were introduced as exercise stimuli. Results At COLPOST visit the secretory IgA (SIgA) concentration in saliva was significantly higher at POST-EX and REC compared to REST (p<0.05). COL supplementation had no effect on blood IgA, IgE, IgD, IgG, and IgM concentrations. Furthermore, after COL supplementation decrease of hematocrit at REC (p<0.05) was revealed. Conclusions 12-week supplementation with 25 gCOL·day-1 in endurance-trained male athletes resulted in a favorable increase in post-exercise concentration of salivary SIgA. COL seems to be a potential stimulator of local immune defense after exercise-induced homeostasis disturbances. Nevertheless, the lack of effect on blood markers indicates the need for further research in the area of mechanisms underlying the effect of the supposed COL immunological capacity.